Hold Your Nose and Vote : Why Do Some Democracies Tolerate Corruption? - Pani, Marco (Washington, D.C. : International Monetary Fund, 2009)
This paper analyses why corruption can persist for long periods in a democracy and inquires whether this can result from a well-informed rational choice of the citizens. By applying a citizen-candidate model of representative democracy, the paper analyzes how corruption distortsthe allocation of resources between public and private expenditure, altering the policy preferences of elected and nonelected citizens in opposite directions. The result is a reduction in real public expenditure and, if the median voter's demand for public goods is sufficiently elastic, a tax reduction. In this case, some citizens can indirectly benefit from corruption. The paper shows that, under this condition, if the citizens anticipate a shift in policy preferences in favor of higher public expenditure, they may support institutional arrangements that favor corruption (such as a weak enforcement of the law) in order to alter future policy decisions in their favor. This result complements the findings of other studies that have attributed the persistence of corruption in a democracyto some failure on the part of the voters or the electoral system. It also bears implications for developing effective anticorruption strategies and for redefining the role that can be played by the international community.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet